Sense-making in the time of COVID-19: a study on the information needs of patients at the moment of confirmation - Abad, Einor John Godfrey L.
With the emergence of a global pandemic, this study aimed to find out how patients made sense of their situation upon finding out that they were positive for Covid-19. This study is heavily influenced by the sense-making model of Brenda Dervin, which divides the sense-making process of an individual into three main. components: the situation, Gap, and Use. Through these three parts, the study was able to find out the information needs and seeking strategies of Covid-19 patients.